ESTUDIO COMPARATIVO DE LA DIGESTIBILIDAD DE FORRAJES MEDIANTE DOS MÉTODOS DE LABORATORIO - Arce P., Carla (2003)
The objective of this study was to standardize the enzymatic procedure for estimating the digestibility of forages using the fungal cellulase Penicillium funiculosum, and its comparison with the Tilley and Terry (1963) in vitro digestibility method. The wellknown in vitro digestibility of alfalfa and oat straw were used for the standardization of the technique. Different quality forages from various locations of Peru were used for the comparison between methods. The best enzyme-substrate concentrations were 200 and 250 mg respectively. Both methods were statistically different, being the enzymatic digestibility values lower than the in vitro method ones. The correlation coefficient between methods was 0.987 (p<0.001). The enzymatic digestibility method proved to be a simple and rapid laboratory analysis for the evaluation of forages.